Differential Expression of -Associated Genes in Autosomal Dominant Polycystic Kidney Disease - Yeon Joo Yook; Yu Mi Woo; Moon Hee Yang; Je Yeong Ko; Bo Hye Kim; Eun Ji Lee; Eun Sun Chang; Min Joo Lee; Sunyoung Lee; Jong Hoon Park (Genomics & Informatics)
Autosomal dominant polycystic kidney disease (ADPKD) is characterized by formation of multiple fluid-filled cysts that expand over time and destroy renal architecture. The proteins encoded by the PKD1 and PKD2 genes, mutations in which account for nearly all cases of ADPKD, may help guard against cystogenesis. Previously developed mouse models of PKD1 and PKD2 demonstrated an embryonic lethal phenotype and massive cyst formation in the kidney, indicating that PKD1 and PKD2 probably play important roles during normal renal tubular development. However, their precise role in development and the cellular mechanisms of cyst formation induced by PKD1 and PKD2 mutations are not fully understood. To address this question, we presently created Pkd2 knockout and PKD2 transgenic mouse embryo fibroblasts. We used a mouse oligonucleotide microarray to identify messenger RNAs whose expression was altered by the overexpression of the PKD2 or knockout of the Pkd2. The majority of identified mutations was involved in critical biological processes, such as metabolism, transcription, cell adhesion, cell cycle, and signal transduction. Herein, we confirmed differential expressions of several genes including aquaporin-1, according to different PKD2 expression levels in ADPKD mouse models, through microarray analysis. These data may be helpful in PKD2-related mechanisms of ADPKD pathogenesis.